2022
DOI: 10.3390/ani12223101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Phosphorus Levels on Growth Performance, Phosphorus Utilization and Intestinal Calcium and Phosphorus Transport-Related Genes Expression of Juvenile Chinese Soft-Shelled Turtle (Pelodiscus sinensis)

Abstract: A 60-day feeding trial was performed to assess the effects of dietary phosphorus levels on growth performance, body composition, phosphorus utilization, plasma physiological parameters and intestinal Ca and P transport-related gene expression of juvenile Chinese soft-shelled turtle (P. sinensis). Four diets containing available P at graded levels of 0.88%, 1.00%, 1.18% and 1.63% (termed as D0.88, D1.00, D1.18 and D1.63, respectively) were formulated and each diet was fed to turtles (5.39 ± 0.02 g) in sextuplic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…Higher diet intake equates to faster digesta transit, which can result in a lower digestive efficiency [ 63 ]. Therefore, the reduction of AD m and AD e of A. japonicus in the present study may result from high feed intake, which agrees with the report on turtle Pelodiscus sinensis [ 64 ]. In addition, apparent digestibility was also indicator of the balance of nutrient deposition and excretion.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Higher diet intake equates to faster digesta transit, which can result in a lower digestive efficiency [ 63 ]. Therefore, the reduction of AD m and AD e of A. japonicus in the present study may result from high feed intake, which agrees with the report on turtle Pelodiscus sinensis [ 64 ]. In addition, apparent digestibility was also indicator of the balance of nutrient deposition and excretion.…”
Section: Discussionsupporting
confidence: 92%
“…Induction and secretion of phosphatase is one of the important adaptive responses of the animal to low phosphorus status. Studies with abalone [ 25 ] and turtle Pelodiscus sinensis [ 64 ] demonstrated that the tissue activity of alkaline phosphatase is negatively correlated with dietary phosphorus levels. However, the present study showed that dietary phosphorus-stimulated intestinal phosphatase activity as dietary phosphorus level increased up to 0.62%.…”
Section: Discussionmentioning
confidence: 99%
“…It facilitates the hydrolysis of phosphate into phosphoric acid under alkaline conditions. Various forms of ALP, including small intestine ALP and bone-type ALP, contribute to the regulation of intestinal function, as well as calcium and phosphorus metabolism [44,45]. DiLorenzo and McCarthy, among others, have provided evidence suggesting that AMY may potentially accelerate the rate of ruminal carbohydrate degradation [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…The main nutritional components of the enzymatic cottonseed protein used in the experiment are 62% crude protein and 0.4% crude lipid. The formula was designed according to the nutritional requirements of Chinese soft-shelled turtle [27][28][29][30]. The experimental feed was prepared with fish meal as the protein source, wheat meal as the sugar source, and soybean oil as the fat source.…”
Section: Experimental Ingredients and Dietsmentioning
confidence: 99%